1989
DOI: 10.1002/tl.37219893904
|View full text |Cite
|
Sign up to set email alerts
|

Socialization of teaching assistants

Abstract: Socialization of TAs occurs through a process of communication as newcomers learn what it means to be teachers as well as graduate students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 5 publications
1
35
0
Order By: Relevance
“…This article contributes to our understanding of how graduate school functions as a socialization process for those who aspire to the academic career, identifying the gaps or discrepancies in that socialization process. The study discussed in this article was guided by the view that socialization is a dialectical process through which newcomers construct their particular roles as they interact and engage with others (Staton & Darling, 1989;Staton-Spicer & Darling, 1986Zeichner, 1980). Socialization is a two-way process where individuals both influence the organization and are influenced by it (Tierney & Bensimon, 1996).…”
Section: Graduate Education As Socialization To the Academic Careermentioning
confidence: 99%
See 1 more Smart Citation
“…This article contributes to our understanding of how graduate school functions as a socialization process for those who aspire to the academic career, identifying the gaps or discrepancies in that socialization process. The study discussed in this article was guided by the view that socialization is a dialectical process through which newcomers construct their particular roles as they interact and engage with others (Staton & Darling, 1989;Staton-Spicer & Darling, 1986Zeichner, 1980). Socialization is a two-way process where individuals both influence the organization and are influenced by it (Tierney & Bensimon, 1996).…”
Section: Graduate Education As Socialization To the Academic Careermentioning
confidence: 99%
“…The socialization process involves learning about the culture of the group, including its values, attitudes, and expectations (Corcoran & Clark, 1984;Staton & Darling, 1989;Van Maanen, 1976). Graduate students experience several socialization processes simultaneously: socialization to the role of graduate student, socialization to the academic life and the profession, and socialization to a specific discipline or field (Golde, 1998;Staton & Darling, 1989). Golde (1998) has argued that graduate students face four general socialization tasks.…”
Section: Graduate Education As Socialization To the Academic Careermentioning
confidence: 99%
“…Prior studies have found that graduate students are motivated to become faculty out of the love of teaching (Golde & Dore, 2001). Teaching typically involves a major time commitment and can detract from time available for research and other activities (Staton & Darling, 1989), so it is possible that experience with teaching has called into question the ability to balance the work requirements of an academic position.…”
Section: Discussionmentioning
confidence: 99%
“…The implication of these students' perspectives about the importance of communication is that interpersonal and small group communication skills are at least, if not more, important than the public speaking skills typically taught in fundamental oral communication courses. In order to survive the larger, more distant, and diverse settings of college life as opposed to high school, freshmen need information seeking skills and strategies, such as attending to and listening to instructions, asking questions, and asserting opinions (Jablin, 1982(Jablin, , 1987Miller &Jablin, 1987;Staton & Darling, 1989;Staton-Spicer &Spicer, 1987).…”
Section: Implications For Communication Educatorsmentioning
confidence: 98%